Trimetazidine Attenuates Cardiac Dysfunction in Endotoxemia and Sepsis by Promoting Neutrophil Migration - Chen, Jing; Wang, Bei; Lai, Jinsheng; Braunstein, Zachary; He, Mengying; Ruan, Guoran; Yin, Zhongwei; Wang, Jin; Cianflone, Katherine; Ning, Qin; Chen, Chen; Wang, Dao Wen (Frontiers in Immunology, 2018)
Aims: Cardiac dysfunction can be a fatal complication during severe sepsis. The migration of neutrophils is significantly impaired during severe sepsis. We sought to determine the role of trimetazidine (TMZ) in regulation of neutrophil migration to the heart in a mouse model of sepsis and endotoxemia, and to identify the mechanism whereby TMZ confers a survival advantage. Methods and Results: C57/BL6 mice were (1) injected with LPS followed by 24-h TMZ administration, or (2) treated with TMZ (20 mg/kg/day) for 1 week post cecal ligation and puncture (CLP) operation. Echocardiography and Millar system detection showed that TMZ alleviated cardiac dysfunction and histological staining showed the failure of neutrophils migration to heart in both LPS- and CLP-induced mice. Bone marrow transplantation revealed that TMZ-pretreated bone marrow cells improved LPS- and CLP-induced myocardial dysfunction and enhanced neutrophil recruitment in heart. In CXCL2-mediated chemotaxis assays, TMZ increased neutrophils migration via AMPK/Nrf2-dependent up-regulation of CXCR2 and inhibition of GRK2. Furthermore, using luciferase reporter gene and chromatin immunoprecipitation assays, we found that TMZ promoted the binding of the Nrf2 and CXCR2 promoter regions directly. Application of CXCR2 inhibitor completely reversed the protective effects of TMZ in vivo. Co-culture of neutrophils and cardiomyocytes further validated that TMZ decreased LPS-induced cardiomyocyte pyroptosis by targeting neutrophils. Conclusion: Our findings suggested TMZ as a potential therapeutic agent for septic or endotoxemia associated cardiac dysfunction in mice. STUDY HIGHLIGHTS What is the current knowledge on the topic? Migration of neutrophils is significantly impaired during severe sepsis, but the underlying mechanisms remain unknown. What question did this study address? The effects of TMZ on cardiac dysfunction via neutrophils migration. What this study adds to our knowledge TMZ attenuated LPS-induced cardiomyocyte pyroptosis and cardiac dysfunction by promoting neutrophils recruitment to the heart tissues via CXCR2. How this might change clinical pharmacology or translational science Our findings suggested TMZ as a potential therapeutic agent for septic cardiac dysfunction.